ANTENSEDEN PENGEMBANGAN KARIR DI BADAN DIKLAT PROVINSI JAWA TENGAH - Atthathur Massalena; Heru Sulistyo (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2015)
Career development is the process of implementation (implementation) career planning. Employee career development can be done through two pathways, namely through education and training (Training) and through non-training (Weighman, 2002). Career development of an employee to occupy a position position is influenced by factors that include the attitude of employers and co-workers, experience, education, achievement, and factors fate. Research Labbase (2010) mentions factors that consists of education and training (training), work performance, work experience and expertise of employees simultaneously significant effect on career development. The problem that often arises is how to optimize career development in Central Java Training Agency. The results of research that education has positive influence on employee performance, the Training Agency of Central Java Province can develop and improve employee to follow training, Technical Guidance, Courses and Workshops, which is expected by the employees participated in some of these education can improve employee performance; Education positive influence on career development, career development of an employee. Discipline is not able to moderate education on job performance, Career development in Central Java Training Agency can be optimized through increased education, competence and job performance of employees. To enhance the career development of the Province of Central Java Training Agency may consider the education and competence of employees, because the view of the results of the study are positive influence between education and competency to career development.Key words : Antenseden Career Development in Central Java Training Agency